Utilization of E-PPGBM for analysing the relation between Posyandu visits post-covid-19 adaptation and low body weight history with stunting among toddlers in semarang city - Larasati, Erika Nurul; Dieny, Fillah Fithra; Rahadiyani, Ayu; Purwanti, Rachma (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2025)
Background: Stunting is a failure in growth and development among children, influenced by various factors such as birth condition and health services. After the Covid-19 pandemic in Indonesia, mothers’ perspectives on Posyandu have changed, and data entry in the e-PPGBM, an application for recording and reporting community-based nutrition,has increased, particularly in Semarang City.Objective: The study aimed to utilize e-PPGBM to analyze the relationship between Posyandu visits post-Covid-19 adaptation and low birth weight (LBW) with stunting among toddlers in Semarang City. Materials and Methods:This case-control study used secondary data from e-PPGBM in Semarang City. The case and control groups each included 1,153 gender-matched toddlers aged 12-59 months as of December 2022. The independent variables were Posyandu visits post-Covid-19 adaptation and low birth weight (LBW). The confounding variables included vitamin A supplementation, birth length, early initiation of breastfeeding (EIBF), birth order, and age. Analysis was conducted for bivariate with chi squares and multivariate with logistic regression.Results: Posyandu visits post-Covid-19 adaptation, LBW and EIBF were not associated with stunting. However, incomplete vitamin A supplementation (OR=0.66, 95% CI=0.54-0.81), short birth length (OR=2.39, 95% CI=1.74-3.27), third or higher birth order (OR=1.52, 95% CI=1.15-2.01), children aged 24-35 months (OR=1.85, 95% CI=1.36-2.53), and children aged 36-47 months (OR=1.58, 95% CI=1.16-2.16) were associated with stunting. Conclusion: Non-routine visits to Posyandu post-Covid-19 adaptation and LBW were higher among toddlers with stunting than normal toddlers. However, this relationship was not significantly related to stunting in Semarang City in December 2022.